Bingkai Pemberitaan Reklamasi Teluk Benoa, Bali 1- 10 Agustus 2013 - Mia Angeline; Lidia Wati Evelina (Bina Nusantara University, 2014)
With the goal of increasing tourism rate, the government plans to reclaim Bali Benoa Bay and Pudut Island to build an integrated tourism area. This plan was rejected by residents fearing the loss of livelihoods and the natural environment is damaged as a result of reclamation, this negative impact was felt when the local government reclaimed the area of Serangan.The purpose of this study was to determine how online media Balipost.co.id and Kompas.com framed the reclamation cases in Bali Benoa Bay. This study used framing analysis, namely by selecting the news published in two online media from August the 1st to 10th, 2013. Result of the study was the differences in the framing of the news. Kompas.com tended to be impartial and focused on the elements of